Some inequalities of Qi type using fractional integration - Dahmani, Zoubir; Belarbi, Soumia (Int. J. Nonlinear Sci, 2010)
In the present paper, we use the Riemann-Liouville fractional integral to establish some integral results for certain classes of functions defined on some intervals of the real line. By introducing parameters 𝛼, 𝛽 and 𝛿, we give some sufficient conditions to generate some fractional inequalities of Qi type, and we give new generalizations for some results of [12,16].
Keywords: Fractional integration, Qi integral inequality